COMPARATIVE CHEMICAL ANALYSIS OF RICE STRAW AND WHEAT STRAW FOR SUSTAINABLE PULP PRODUCTION (Modern American Journal of Biological and Environmental Sciences, 2025)
Agricultural residues such as rice straw and wheat straw represent promising non-wood raw materials for sustainable pulp and paper production. This study presents a comparative chemical analysis of these two lignocellulosic biomasses to evaluate their suitability for environmentally friendly pulping processes. The composition of cellulose, hemicellulose, lignin, ash, and silica content was determined using standardized analytical methods. Results indicated that rice straw contains a higher ash (15.8%) and silica content (10.2%) compared to wheat straw (7.4% and 3.5%, respectively), which can influence pulping chemical consumption and processing efficiency. Conversely, wheat straw exhibited a slightly higher cellulose content (41.6%) than rice straw (38.7%), suggesting a marginal advantage in terms of fiber yield and mechanical strength. Fourier Transform Infrared (FTIR) spectroscopy and Thermogravimetric Analysis (TGA) further revealed structural differences in lignin bonding and thermal stability, which are critical for optimizing pretreatment and chemical recovery steps. Based on the findings, wheat straw appears more favorable for conventional soda or kraft pulping, while rice straw may require silica removal or pretreatment modification to enhance processing efficiency. These insights support the development of tailored pulping strategies for different types of agro-waste, contributing to resource-efficient and low-impact bio-based material production.